2012
DOI: 10.1177/1090820x12436601
|View full text |Cite
|
Sign up to set email alerts
|

Breast Augmentation and Augmentation-Mastopexy With Local Anesthesia and Intravenous Sedation

Abstract: Breast augmentation with or without mastopexy can be performed safely, with minimal discomfort and complications, by employing local anesthesia with intravenous sedation. Although augmentation-mastopexy requires more operating time than augmentation alone, the recovery times are comparable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 17 publications
1
4
1
Order By: Relevance
“…5 Other studies of intercostal nerve block use in breast augmentation have not reported any cases of pneumothorax. 16,25,30 In concordance with the low incidence shown in these previous studies, we encountered only one pneumothorax, which resolved spontaneously and was likely related to simultaneous port placement.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…5 Other studies of intercostal nerve block use in breast augmentation have not reported any cases of pneumothorax. 16,25,30 In concordance with the low incidence shown in these previous studies, we encountered only one pneumothorax, which resolved spontaneously and was likely related to simultaneous port placement.…”
Section: Discussionsupporting
confidence: 90%
“…This differs from previous studies that reported significant postoperative nausea and vomiting reductions in patients receiving intercostal nerve blocks for breast surgery, 24,25 but provides findings similar to other studies that demonstrate no improvement. 20 Those studies that demonstrate reduction in postoperative nausea and vomiting in patients receiving intercostal nerve block used the nerve block as the primary mode of anesthesia (general anesthesia was not used), and those studies demonstrating no improvement in postoperative nausea and vomiting used intercostal nerve block in conjunction with general anesthesia (as was done in our study).…”
Section: Discussioncontrasting
confidence: 84%
“…Some groups have reported low rates (between 10% and 12% of patients) of PONV by performing aesthetic surgery in an office setting using local anesthesia and intravenous sedation. 12 Our study demonstrates a significantly lower rate of PONV (5.6%) with the surgery performed in a surgical facility with all of the advantages of general anesthesia. By using a risk-directed multimodal regimen for antiemetics and analgesics, these procedures can be done under general anesthesia with outcomes that surpass the PONV rate for avoidance of general anesthesia.…”
Section: Discussionmentioning
confidence: 53%
“…The use of local anaesthetic with sedation in breast augmentation surgery is a relatively common practice that also avoids the use of general anaesthesia (Cloque & Michael 2012; Gart et al 2013). In our described technique, no sedation was required and no patients either required the surgery to be abandoned mid procedure or a conversion to a general anaesthetic due to not tolerating the technique.…”
Section: Discussionmentioning
confidence: 99%